2016
DOI: 10.2135/cropsci2015.10.0633
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Genetic Mechanisms Regulating Methionine Concentration in Maize Grain

Abstract: Methionine is a limiting amino acid in poultry diets, so methionine supplementation is typically required to meet nutritional demands. Maize (Zea mays L.) varieties with increased methionine levels have been developed using three different approaches: (i) increased levels of the methionine‐rich 10‐kDa zein, (ii) disruption of protein deposition using the floury‐2 allele, and (iii) recurrent selection. The goal of this study was to characterize the interactions of these three mechanisms for increasing methionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…High narrow (0.75) and broad (0.85) sense heritability values suggest protein concentration can be improved via breeding. High additive gene effects for methionine revealed by Huffman et al (2016) are consistent with our results related to methionine heritability.…”
Section: Analysis Of Variance and Genetic Componentssupporting
confidence: 91%
See 3 more Smart Citations
“…High narrow (0.75) and broad (0.85) sense heritability values suggest protein concentration can be improved via breeding. High additive gene effects for methionine revealed by Huffman et al (2016) are consistent with our results related to methionine heritability.…”
Section: Analysis Of Variance and Genetic Componentssupporting
confidence: 91%
“…Darrigues et al (2005) reported a methionine concentration of 0.210 g / 100 g, in the dzr1 inbred B101. Huffman et al (2016) found this value to be 0.179 g / 100 g in hybrids in diallel crosses in which some parents contained dzr1. Although the findings were similar, relatively higher results were obtained from our study.…”
Section: Mean Grain Yield Quality Characteristics Lysine and Methionine Levels Of The Hybridsmentioning
confidence: 91%
See 2 more Smart Citations